Correlates of Farmers’ Knowledge of Recommended Water Productivity Practices - Hiwarkar, G. R. , P. K. Wakle , A. S. Gomase; Lambe, S. P. (Indian Journal of Extension Education, 2014)
The study was carried out in Buldana and Yavatmal district in Maharashtra state to know the farmers’ knowledge about recommended Water Productivity practices. Krishi Vigyan Kendra, Buldana and Yavatmal were selected purposively as these KVKs have organized trainings on water productivity practices. From each KVK , 25 respondents who attended the trainings were selected randomly. Thus a total 50 respondents were personally contacted for data collection. The study revealed that more than half respondents possessed moderate knowledge about recommended practices of water productivity practices. The relational analysis showed that education qualification, risk reference, sources of information, sources of irrigation and innovativeness were positively correlated with the extent of knowledge of recommended water productivity practices by the respondents.